Mapping Research on Immersive Learning Technologies in Science Education: A Bibliometric Analysis of VR–AR–MR Studies - Ahmad Syaiful Anwar; Annastasya Syafitri; Dwi Astuti; Slamet Suyanto (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2025)
Despite the growing prominence of immersive technologies in educational contexts, a comprehensive bibliometric examination of Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR) within science education remains notably underrepresented in the literature. This study addresses that gap by conducting a quantitative bibliometric analysis to systematically map the broad landscape of immersive learning research in science education. Data were retrieved from the Scopus database and filtered in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, yielding a final corpus of 188 articles for analysis. Bibliometric processing and visualization were performed using Biblioshiny software. The findings reveal that immersive learning research has transitioned from an initiation phase to a period of exponential growth, particularly between 2020 and 2025. Virtual Reality emerged as the dominant technology within this domain, with Augmented Reality and science education serving as primary enablers of interactive learning environments. Prominent keywords, including students, education, and e-learning, collectively underscore a sustained research focus on enhancing conceptual understanding, learner engagement, and overall learning experiences. Geographically, scholarly output is heavily concentrated in the United States, Germany, and China, a pattern attributable to the concentration of immersive technology developers, differential research funding structures, policy orientations, and national education priorities. Notably, the relatively modest international collaboration rate of 22.34% signals considerable untapped potential for cross-national research partnerships. These findings collectively offer a strategic roadmap for advancing innovation at the intersection of immersive technology and pedagogy, while underscoring the imperative for strengthened cross-institutional and international scholarly collaboration.